Toward a just pedagogy of performance
1 online resource.
Keywords: "This book is a compendium of resources largely by and for artists and scholars interested in engaging in conversations of justice, diversity, and historiography in the fields of theatre and performance studies. For these students, and for the future instructors in our field who will use this book, we hold a tripartite hope: to expand, to enable, and to provide access. In its whole, we intend for this book to provoke its readers to question the narratives of history that they've received (and that they may promulgate) in their artistic and scholarly work. We aim to question methods and ethics of reading present in the western mode of studying drama and performance history. The contributions in the book-not traditional chapters, but manifestos, experiences, articles, conversations, and provocations-raise questions and illuminate gaps, and they do not speak in a unified voice or from a static position. These pieces are written by artists, graduate students, teachers, administrators, and undergraduates; these are expressions of hope and of experience, and not of dogma. This book is aimed toward instructors of undergraduates, both graduate students and faculty at all levels of seniority within theatre and performance studies, as well as at artists and practitioners of the art that wish to find more just ways of viewing history"--